A novel porous‐dense dual‐layer composite membrane reactor with long‐term stability. Issue 11 (12th July 2013) - Jiang, Wei; Zhang, Guangru; Liu, Zhengkun; Zhang, Kai; Jin, Wanqin
<x xml:space="preserve">Abstract</x> A porous‐dense dual‐layer composite membrane reactor was proposed. The dual‐layer composite membrane composed of dense 0.5 wt % Nb2O5‐doped SrCo0.8Fe0.2O3‐δ (SCFNb) layer and porous Ba0.3Sr0.7Fe0.9Mo0.1O3‐δ (BSFM) layer was prepared. The stability of SCFNb membrane reactor was improved significantly by the porous‐dense dual‐layer design philosophy. The porous BSFM surface‐coating layer can effectively reduce the corrosion of the reducing atmosphere to the membrane, whereas the dense SCFNb layer permeated oxygen effectively. Compared with single‐layer dense SCFNb membrane reactor, no degradation of performance was observed in the dual‐layer membrane reactor under partial oxidation of methane during continuously operating for 1500 h at 850°C. At 900°C, oxygen flux of 18.6 mL (STP: Standard Temperature and Pressure) cm−2 min−1, hydrogen production of 53.67 mL (STP) cm−2 min−1, CH4 conversion of 99.34% and CO selectivity of about 94% were achieved. © 2013 American Institute of Chemical Engineers AIChE J, 59: 4355–4363, 2013